Cell suspension culture and plant regeneration of a Brazilian plantain, cultivar Terra - Morais-Lino, Lucymeire Souza; Santos-Serejo, Janay Almeida dos; Silva, Sebastião de Oliveira e; Santana, José Raniere Ferreira de; Kobayashi, Adilson Kenji (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this study was to establish cell suspension culture and plant regeneration via somatic embryogenesis of a Brazilian plantain, cultivar Terra Maranhão, AAB. Immature male flowers were used as explant source for generating highly embryogenic cultures 45 days after inoculation, which were used for establishment of cell suspension culture and multiplication of secondary somatic embryos. Five semisolid culture media were tested for differentiation, maturation, somatic embryos germination and for plant regeneration. An average of 558 plants per one milliliter of 5% SCV (settled cell volume) were regenerated in the MS medium, with 11.4 µM indolacetic acid and 2.2 µM 6-benzylaminopurine. Regenerated plants showed a normal development, and no visible somaclonal variation was observed in vitro. It is possible to regenerate plants from cell suspensions of plantain banana cultivar Terra using MS medium supplemented with 11.4 µM of IAA and 2.2 µM of BAP.